Biomass from Palm Oil Waste as a Renewable Energy Source with Community Benefits - Thomas, Schafir; Andres, Csery (International Journal Papier Advance and Scientific Review, 2021)
This article addresses Biomass as a green energy source. The oil palm by-product is commonly accepted as a suitable raw material for power plant diesel. Numerous countries are beginning to transition to palm biomass as a fuel source due to its environmental friendliness and green nature. Renewable energy management needs technology, since it would only be produced to generate energy from natural products that will never run out. Nevertheless, the life of the oil palm plantation itself is very poor. For example, the influence of oil palm plantations on natural capital in green land has decreased or even vanished. Indeed, the biological organisms that inhabit it are the primary source of life for the population, especially the indigenous people who live in close proximity to the soil.